Comparing the environmental impacts of pollution from two types of industrial zones on the coast - Liang, Jian; Ma, Chae-Woo; Kim, Kwang-Bae (Frontiers in Marine Science, 2024)
Introduction The construction of coastal industrial zones has significantly impacted the marine environment, with the extent of these effects varying based on the type of industrial activity. This study compares the environmental impact of two prevalent types of industrial zones along South Korea’s coast: ironworks and shipyards. Methods We assessed heavy metal pollution near these industrial zones using the Pollution Load Index (PLI) and Nemerow Pollution Index (Pn). To evaluate the impact of heavy metals and organic matter on macrobenthic communities, we employed redundancy analysis (RDA) and Spearman correlation analysis. Additionally, we used the AZTI’s Marine Biotic Index (AMBI), Multivariate AMBI (M-AMBI), and Benthic Pollution Index (BPI) to gauge the ecological quality of the affected marine environments. Results and discussion Our findings indicated that the biodiversity and abundance of species near shipyards were significantly lower than those near ironworks. Results of PLI and Pn revealed that the ecological risk posed by heavy metals from shipyard activities was significantly higher than from ironworks. The AZTI’s Marine Biotic Index (AMBI), Multivariate AMBI (M-AMBI), and Benthic Pollution Index (BPI) demonstrated that the ecological quality of Asan Bay (ironworks) is better than that of Dangdong Bay (shipyard). RDA analysis identified Lumbrineris longifolia, Ancistrosyllis hanaokai, and Theora fragilis as biological indicators for assessing heavy metal and organic matter pollution. Spearman correlation analysis indicated that BPI and species richness index are effective indicators for evaluating such pollution. Overall, the negative impact of shipyards on the marine environment was significantly more significant than that of ironworks. Our study provides valuable insights for the South Korean government in managing coastal industrial zones and formulating relevant policies.